Single 5 Gy Dose and the Immune System: Cd-Profile Dynamics and Probiotic Correction Opportunities - Kh. Kh., Tukhtaeva (American Journal of Biomedicine and Pharmacy, 2025)
The aim of the study was to determine the effect of acute irradiation on the immune status of experimental animals, taking into account the degree of influence of biocorrection on this process. It was found that in white outbred male rats that received and did not receive acute irradiation, distinctive results were obtained in the relative values of immune system cells. This was observed in the total number of lymphocytes, cells - CD3+-, CD4+- and CD8+. A key indicator of the development of secondary immunodeficiency is a decrease in IRI by 2.01 times in the main group. No changes were found in CD20+ cells, in the main group of laboratory animals the number of CD16+ cells increased by 1.35 times, and in CD95+ cells it decreased by 1.51 times. The deficiency of the immune system in the biocorrection group was relatively shallow, the biological product used had an immunostimulating effect. It has been proven that its use reduced the negative impact of acute irradiation on the quantitative indicators of immune system cells.